Convex vNM-stable sets for a semi orthogonal game. Part II: Rich central commodity - Joachim Rosenmüller (Bielefeld University, Center for Mathematical Economics (IMW), 2014)
This paper constitutes the second part in a series dealing with vNM-Stable sets for (cooperative) linear production games with a continuum of players, see [2]. The coalitional function is generated by r + 1 production factors (non atomic measures). R factors are given by orthogonal probabilities (cornered production factors) while factor r + 1^th is provided across the corners of the market. We consider convex vNM-Stable Sets of this game. Within the second part we present an economy reflecting relative abundance of the central commodity. In this situation the model allows for a vNM-Stable Set including but not equal to the core of the game. Rather there is an additional imputation such that the vNM-Stable Set is the convex hull of this imputation and the core. This imputation is essentially described by the density of the r + 1^st production factor - mutatis mutandis.
urn:nbn:de:0070-pub-26753291
Keywords: 330